Perbedaan Pemahaman Pengobatan Mandiri Antara Pengguna Obat Tradisional Dan Pengguna Obat Sintetik Di Masyarakat Kota Denpasar - Ni Luh Nyoman Ari Mayoni; Arimbawa, Putu Eka; Made Aman, I Gusti (Bali International Scientific Forum, 2022)
Abstract Background: Drugs are defined as compounds used to diagnose diseases or disorders treat, prevent, and it became an irreplaceable component in health services. Drugs be divided into 2 types, namely traditional drugs and synthetic drugs. There are many types of drugs circulating in the market, people must be more selective in choosing the type of drug for the disease or complaint they are experiencing. Therefore, the understanding of self-medication is very important to form action, including the use of drugs. Purpose: This study was to determine the differences in the understanding of self-medication between traditional medicine users and synthetic medicine in the community of Denpasar City. Method: The research design used in this study is descriptive-analytic with a cross sectional research design. The number of samples taken was 100 respondents by purposive sampling. Measurements are carried out using questionnaires. The data analysis technique used in this study is Mann-Whitney. Result: The results used analysis Mann-Whitney test showed a p-value of 0.0001, which means that there are differences in the understanding of self-medication between traditional medicines users and synthetic medicines users. Conclusion: That there are differences in the understanding of self-medication between traditional medicines users and synthetic medicines users in the people of Denpasar City. Keywords: traditional medicine, synthetic medicine, self-medication